Efek Antiaterogenik Ekstrak Pakis Sayur (Diplazium esculentum) melalui Penghambatan Vascular Cell Adhesion Molecule-1 pada Tikus Model Aterogenik - Tristira Urvina; Erma Sulistyaningsih; Ika Rahmawati Sutejo (Universitas Malahayati Lampung, 2022)
ABSTRACT Atherosclerosis is one cause of death. The thickening of the arterial walls which form atherosclerotic plaque can cause a blockage of the artery lumen and lead to thrombosis and blood flow. VCAM-1 activation causes increased adhesion of monocytes to endothelial walls and foam cell formation which is the key to the occurrence of atherosclerosis. Diplazium esculentum contains antioxidants and is able to inhibit the activation of VCAM-1. This study aimed to determine the effect of vegetable fern extract on the expression of VCAM-1 as an anti-atherogenic effect and the effective dose required. Experimental studies using randomized post test only control group design. Samples were grouped into 7 groups, namely K, KN, P1, P2, P3, P4, and P5. All group except K induced by atherogenic diet ang followed by the granting of vegetable fern extracts of 300 mg/kgBW in P1 groups, 600 mg/kgBW in P2 groups, 900 mg/kgBW in P3 groups, 1200 mg/kgBW in P4 groups, and 1500 mg/kgBW in P5 groups. The results showed a correlation between the dose of the extract given by the expression of VCAM-1, the greater the dose given VCAM-1 will be further hampered. The effective dose in rats was 2707, 19 mg/kg, this dose is equivalent to 4 kg of fresh vegetables fern in humans. Keywords: Atherosclerosis, Vegetable Fern Extract, VCAM-1 ABSTRAK Aterosklerosis merupakan salah satu penyebab kematian. Penebalan dinding arteri yang membentuk plak aterosklerosis dapat menyebabkan penyumbatan lumen arteri dan mengakibatkan trombosis dan gangguan aliran darah. Aktivasi VCAM-1 menyebabkan peningkatan perlekatan monosit pada dinding endotel dan pembentukan foam cell yang merupakan kunci terjadinya aterogenesis. Diplazium esculentum mengandung senyawa aktif yang bersifat antioksidan dan mampu menghambat aktivasi VCAM-1. Penelitian ini bertujuan untuk mengetahui pengaruh ekstrak pakis sayur terhadap ekspresi VCAM-1 sebagai efek antiaterogenik dan dosis efektif yang diperlukan. Studi eksperimental menggunakan randomized post test only control group design. Sampel dikelompokkan menjadi 7 kelompok, yaitu K, KN, P1, P2, P3,P4, dan P5. Tiap kelompok diinduksi diet aterogenik dilanjutkan dengan pemberian ekstrak pakis sayur sebesar 300 mg/kgBB, 600 mg/kgBB, 900 mg/kgBB, 1200 mg/kgBB, dan 1500 mg/kgBB. Hasil penelitian menunjukkan terdapat hubungan antara dosis ekstrak yang diberikan dengan ekspresi VCAM-1, semakin besar dosis yang diberikan ekspresi VCAM-1 akan semakin terhambat. Dosis efektif pada tikus adalah 2707, 19 mg/kgBB, dosis ini setara dengan 4 kg pakis sayur segar pada manusia. Kata Kunci: Aterosklerosis, Ekstrak Pakis Sayur, VCAM-1